2019
DOI: 10.1002/lpor.201900006
|View full text |Cite
|
Sign up to set email alerts
|

A Photostimulated BaSi2O5:Eu2+,Nd3+ Phosphor‐in‐Glass for Erasable‐Rewritable Optical Storage Medium

Abstract: Up‐to‐date optical storage technology calls for large memory capacity, expanded storage dimension, rewritable capability, low cost, and high energy efficiency, which poses stringent requirements on the storage medium. In this study, a novel BaSi2O5:Eu2+,Nd3+ photostimulated luminescence (PSL) phosphor is developed and then made into phosphor‐in‐glass (PiG) storage medium. Upon ultraviolet light irradiation (write‐in), the generated electrons are captured by the traps, which can be further released by thermal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Barium silicates are extensively studied for their excellent material properties and device performance in a range of important technological applications [1][2][3][4][5][6][7] Sanbornite (low-BaSi2O5) is a uncommon mineral found in Big Creek, California (USA), and its hydrous analogue bigcreekite (BaSi2O5•4H2O) are rare examples where Ba is concentrated in a silicate phase [8][9][10]. On the other hand, Ba5Si8O21 is a synthetic phase, displaying the rare characteristic of being an anhydrous phase containing ribbons (quadruple zweier chains) of silica tetrahedra surrounded by Ba cations which stabilize the stretched chains.…”
Section: Introductionmentioning
confidence: 99%
“…Barium silicates are extensively studied for their excellent material properties and device performance in a range of important technological applications [1][2][3][4][5][6][7] Sanbornite (low-BaSi2O5) is a uncommon mineral found in Big Creek, California (USA), and its hydrous analogue bigcreekite (BaSi2O5•4H2O) are rare examples where Ba is concentrated in a silicate phase [8][9][10]. On the other hand, Ba5Si8O21 is a synthetic phase, displaying the rare characteristic of being an anhydrous phase containing ribbons (quadruple zweier chains) of silica tetrahedra surrounded by Ba cations which stabilize the stretched chains.…”
Section: Introductionmentioning
confidence: 99%
“…Photostimulated luminescence (PSL) phosphors can store excitation energy and release it as light emission upon infrared light irradiation. [1][2][3][4][5] The physical origin of PSL is similar to that of persistent luminescence (PersL) except that the traps of PSL materials are deeper than those of their PersL analogs, which cannot be thermally activated at room temperature. [6][7][8][9] Over the past decades, numerous efforts have been devoted to the design of efficient PSL phosphors for applications in radiation dosimeters, optical storage, infrared sensors, and luminescent paints.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Lin et al reported BaSi 2 O 5 :Eu 2+ , Nd 3+ PiG with OSL property for optical encoding/decoding. [96] The upper panel of Figure 24d shows the whole domain read-out of the stored information from the OSL PiG plate which was preirradiated by UV light through photomasks with designed patterns. Meanwhile, a further proof-of-concept implementation of optical write-in and read-out in bit-by-bit mode was also carried out.…”
Section: Encryption and Decryptionmentioning
confidence: 99%
“…Reproduced with permission. [96] Copyright 2019, Wiley-VCH. The dosimeter is initially scanned with the red laser sheet for OSL signal, then with the UV source for PL signal.…”
Section: Challenges and Outlooksmentioning
confidence: 99%